SAT0586 Ultrasonographic Signs Of Inflammation of Metatarsophalangeal Joints in Rheumatoid Arthritis Patients who are Treated to Target. (9th June 2015) - van der Ven, M.; Ten Cate, D.; Gerards, A.; Jacobs, H.; Swen, N.; de Jager, M.; Basoski, N.; Haagsma, C.; Hazes, M.; Luime, J.
Abstract : Background: The feet are often involved in rheumatoid arthritis (RA), but physical examination of the metatarsophalangeal (MTP) joints to detect arthritis is always challenging especially in case of obesity, oedema and malalignment. Ultrasound (US) has proven to be more sensitive than physical examination to detect (subclinical) synovitis in the MTP joints. Objectives: (i) To determine the frequency of subclinical synovitis in the MTP joints by US among patients in DAS28 remission or LDA, and (ii) to assess discordance between the evolution of US arthritis in the feet and DAS28 over time in newly diagnosed RA patients who are treated to target. Methods: A multicentre cohort of newly diagnosed RA patients was followed prospectively for one year. Patients were treatment naïve for synthetic DMARDs, biological DMARDs and glucocorticoids, and symptom duration was less than one year. All patients were treated to target with regular visits. Demographics, clinical (SJC28, TJC28) and laboratory (ESR, RF, ACCP) parameters were recorded at each visit. US examination of the dorsal aspect of MTP2-5 joints was performed at baseline, three months and one year. Images were scored on greyscale (GS; 0-3) and power Doppler (PD; 0-3). A US positive MTP joint was defined by GS>1 and/or PD>0. Simple descriptive statistics were used and longitudinal course of both DAS28 and number of US positive MTP joints were plotted for each patient. Discordance of course was defined as crossing of slopes. Results: At baseline, 174 patients were included of whom 159 completed one year follow-up. At baseline, 109 (73%) patients had at least one US positive MTP joint. Overall, mean (SD) DAS28 decreased from 4.9 (1.3) at baseline to 2.3 (1.2) at one year, while the number of US positive MTP joints decreased from median (interquartile range) 1 (0-4) at baseline to 0 (0-0) at one year. Discordance in longitudinal course of DAS28 and US positive MTP joints over one year was seen in 9 patients (6%). After one year of follow-up, 98 (62%) patients were in DAS28 remission (DAS28<2.6) of whom 23 (23%) still had at least one US positive MTP joint. Twenty-nine patients had low disease activity (DAS28≤3.2) of whom 7 (24%) had at least one US positive MTP joint. Conclusions: Most patients (94%) improved both in DAS28 score and number of US positive MTP joints during follow-up. However, 23% of the early RA patients in DAS28 remission still had subclinical synovitis on US in at least one MTP joint at one year. Monitoring of MTP joints by US and subsequent steering of treatment might be considered to prevent for example progressive radiological damage. Disclosure of Interest: None declared